Street Stories: Can We Go Higher? A Song for the Victims of War
Documentary about Nenad Bach, a Croatian-American musician who brought together well known actors and artists to call for an end to the war in the former Yugoslavia. "Can We Go Higher?" was the song that has been released to raise humanitarian aid for the victims of the war in Croatia and Bosnia & Herzegovina.